Globalisation - a threat to traditional landscapes and local identity? - Helen Alumäe; Hannes Palang; Helen Sooväli (European Regional Science Association (ERSA), 2001)
Traditional landscapes could be considered as one of the most apparent carriers of local identities. They act as memory of previous human activities. During the 1990s the economic changes have had a drastic influence on the appearance of these landscapes. On one hand, local people are keen to keep the existing patterns that indicate their feeling of belonging. On the other hand, there is a desire to introduce new patterns dictated by new technologies, economic conditions, enlarged knowledge. This might lead to a kind of standardized landscape so that one cannot distinguish between, e.g., Denmark and western Estonia. The presentation will focus on the local identities in three Estonian counties. We deal with locals' preferences and ideas concerning their landscapes. Based on some 400 interviews we try to investigate which is the role of traditional landscape in local life, what kind of landscape changes are seen by locals as acceptable, what trade-offs are possible on landscape development, how could local people be involved in landscape planning, do current economic policies support or harm the maintenance of the traditional landscape.
Keywords: 330